Proposal of new Natura 2000 network boundaries in Spain based on the value of importance for biodiversity and connectivity analysis for its improvement. (October 2021) - Rincón, Víctor; Velázquez, Javier; Gutiérrez, Javier; Hernando, Ana; Khoroshev, Alexander; Gómez, Inmaculada; Herráez, Fernando; Sánchez, Beatriz; Pablo Luque, Juan; García-abril, Antonio; Santamaría, Tomás; Sánchez-Mata, Daniel
Highlights: Criteria and indicators for location of Natura 2000 are presented. Connectivity of Natura 2000 spaces is essential for their conservation. Improvement of connectivity of protected areas is assessed with MSPA and PC indices. Assessment of connectivity is necessary for management and conservation of Natura 2000 Network. Abstract: The aim of the Natura 2000 Network is to ensure the conservation of habitats and species in their natural areas of distribution. Connectivity is an essential part of this conservation. For this purpose, a value map of importance for biodiversity (V.I.B) was generated proposing 4 levels of protection and overlapped with the Natura 2000 network. New boundaries for the zoning are proposed adding 1.600.000 ha. Two connectivity indices (MSPA and PC) are calculated in the 4 different scenarios. With these indices it is possible to know the number of existing nuclei and connectors in each of the scenarios. New boundaries cover more areas of interest for biodiversity as well as zones of great importance in relation to connectivity. We propose a uniform method that can be extrapolated to any European territory.